TURKISH NOTIFICATION LAW - Akcan, Recep (European Scientific Journal, ESJ, 2012)
ï»¿Notice Law is an important law because, apart from specific regulations in other laws, it is applied in different kinds of legal procedures such as judicial, administrative and military procedures and is related to legal right of hearing, the right of prosecution and defense and the right to a fair trial. Turkish Notice Law took effect in 1959. Before this date, provisions concerning notice were codified in the Code of Civil Procedure. From this date on, there has been a separate Notice Law. Some amendments have been made in this law until today. The latest amendments took place on January 10, 2011. Therefore, it was deemed useful that these latest changes in the Notice Law should be investigated. The Article is going to do a thorough investigation of the issue in Turkish Civil Law and specifically focusing on these new changes.